THE IMPACT OF THE APPLICATION OF KAHOOT DIGITAL TECHNOLOGY ON LEARNING OUTCOMES OF STUDENTS AT SDN 49/III KOTO BARU S. AGUNG - hazwa, Wal (Jurnal Ilmiah Didaktika, 2025)
This study investigates the effect of implementing Kahoot digital technology on the cognitive learning outcomes of students at SDN 49/III Koto Baru S. Agung. As technology rapidly advances, game-based platforms such as Kahoot are increasingly recognized for enhancing material comprehension through more interactive pedagogical approaches. This research employs a quantitative approach with a quasi-experimental design, comparing an experimental group that utilizes Kahoot as a learning medium with a control group that uses traditional instructional methods. Results demonstrated that Kahoot yielded statistically significant improvements (p < 0.01) with a substantial practical impact. Effect size analysis (Cohen's d) reached 2.89, indicating a considerable effect, while the Normalized Gain (N-Gain) achieved 0.57, categorized as moderate effectiveness. Kahoot's effectiveness stems from its capacity to trigger intrinsic motivation and foster active engagement, thereby confirming gamification as a superior and adaptive strategy for enhancing cognitive achievement among digital native students at the elementary school level.